Longitudinal associations between 4-hydroxynonenal and depression in coronary artery disease patients. (December 2018) - Rosen, Michael; Chan, Parco; Saleem, Mahwesh; Herrmann, Nathan; Adibfar, Alexander; Andreazza, Ana; Oh, Paul I.; Lanctôt, Krista L.
Highlights: Depression is an independent predictor of poorer outcomes in patients with CAD. Antidepressants are modestly effective; oxidative stress (OS) may be a novel target. 4-HNE, an OS marker, was increased in CAD patients with depression despite exercise. A decrease in 4-HNE was associated with an improvement in depressive symptoms. 4-HNE may predict depression in CAD; 4-HNE activity may be a future drug target. Abstract: Depressive symptoms in patients with coronary artery disease (CAD) attenuate the cardiovascular benefits of cardiac rehabilitation (CR). Given that oxidative stress may be an important mechanism underlying depression, this study aimed to understand the longitudinal relationship between lipid peroxidation markers and depression in CAD. Serum levels of early (lipid hydroperoxides, LPH) and late (4‑hydroxy‑2-nonenal, 4-HNE; 8-isoprotane, 8-ISO) lipid peroxidation markers were measured in 120 CAD patients undergoing CR. The Structured Clinical Interview for DSM Axis I Disorders – Depression Module (SCID) was used to diagnose depression at baseline and the Center for Epidemiological Studies Depression Scale (CES-D) was used to measure depressive symptom severity. Multivariate mixed models compared the trajectories of serum LPH, 4-HNE, and 8-ISO between depressed and non-depressed CAD patients undergoing 6 months of CR. Similar models evaluated the associations between serum LPH, 4-HNE, and 8-ISO and CES-D score over the course of CR. Serum 4-HNE decreased less in CAD patients with depression compared to those without. In addition, a decrease in 4-HNE concentrations was significantly associated with a decrease in CES-D scores over 6 months. These findings suggest that 4-HNE may be an important marker of depressive symptoms in CAD and may be involved in its progression.